(untitled) (Journal of Comparative & International Higher Education, 2021)
Interest in international student identity has grown considerably over the last few years. In the context of international education, the emphasis on identity and the individual student may also be seen as an emerging response to the tendency of discussing international students and their identity-related experiences in homogenising ways. While there is considerable discussion about how international students’ sense of self is affected by cultural differences in higher education, a theory of identity is not always in place. The purpose of this paper is to bring together three theoretical perspectives on identity that are designed to account for specific cultural, social, and linguistic influences on identity construction. These perspectives are examined with examples from data-based case studies. This paper identifies the unique affordances of each perspective while also highlighting their mutual role in challenging broad discourses that have unfavourably defined international student identity.